Mitochondrial dysfunction in diabetic ulcers: pathophysiological mechanisms and targeted therapeutic strategies - Pan, Yu; Chen, Lin; Chen, Yan; Thomas, Elizabeth Rosalind; Zhou, Shiying; Yang, You; Liu, Kezhi; Wu, Jianming; Li, Xiang (Frontiers in Cell and Developmental Biology, 2025)
Diabetic foot ulcers (DFUs) are a serious complication of diabetes, characterized by delayed wound healing, recurrent infection, and risk of amputation. Mitochondrial dysfunction has emerged as a central pathological mechanism underlying impaired wound healing. Persistent hyperglycemia triggers a cascade of mitochondrial abnormalities like disrupted calcium homeostasis, excessive ROS production, impaired autophagy, increased apoptosis, and imbalanced mitochondrial dynamics. These alterations hinder ATP production, damage repair cells and delays tissue regeneration. This review comprehensively explores the mechanism of action of oxidative stress, mitochondrial apoptosis, autophagy dysfunction, calcium imbalance and ferroptosis on DFU pathogenesis. It also highlights promising mitochondrial targeted therapies. As mitochondria regulates key cellular processes, targeting mitochondrial dysfunction represents a novel and promising strategy. Future research should focus on integrated approaches to restore mitochondrial homeostasis in diabetic wound healing.